2018
DOI: 10.3390/ijms19092580
|View full text |Cite
|
Sign up to set email alerts
|

The Maize WRKY Transcription Factor ZmWRKY40 Confers Drought Resistance in Transgenic Arabidopsis

Abstract: Abiotic stresses restrict the growth and yield of crops. Plants have developed a number of regulatory mechanisms to respond to these stresses. WRKY transcription factors (TFs) are plant-specific transcription factors that play essential roles in multiple plant processes, including abiotic stress response. At present, little information regarding drought-related WRKY genes in maize is available. In this study, we identified a WRKY transcription factor gene from maize, named ZmWRKY40. ZmWRKY40 is a member of WRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 60 publications
4
69
0
Order By: Relevance
“…WRKY TFs are one of the largest families of transcriptional regulators in plants, and have multiple developmental and physiological functions in response to environmental stresses [30]. In plants such as rice [31], soybean [16,32], cotton [33], Brachypodium distachyon [34,35], maize [36], and wheat [37], an especially large number of WRKY proteins have been identified in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…WRKY TFs are one of the largest families of transcriptional regulators in plants, and have multiple developmental and physiological functions in response to environmental stresses [30]. In plants such as rice [31], soybean [16,32], cotton [33], Brachypodium distachyon [34,35], maize [36], and wheat [37], an especially large number of WRKY proteins have been identified in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…WRKY transcription factors are one of the largest families of transcriptional regulators in plants, and are involved in the drought-related response [ 27 ]. In plants such as wheat [ 28 ], rice [ 29 ], brachypodium distachyon [ 30 ], maize [ 31 ], soybean [ 32 ], and cotton [ 33 ], a large number of WRKYs have been identified in recent years. In our previous study, we identified that TaWRKY28, TaWRKY33, TaWRKY40, and TaWRKY47 preferentially bind to specific W-box in cw-TaGApC5 ( cw-TaGApC2-6D ) and zy-TaGApC5 ( zy-TaGApC2-6D ) by Y1H and EMSA (Electrophoretic Mobility Shift Assay) analyses [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ancient gene transfer events were considered as the origin of these non-plant WRKYs based on distribution pattern analysis [11]. Numerous WRKY TFs have been experimentally revealed in various plant species, including (Arabidopsis thaliana) [12], sugarcane (Saccharum spontaneum) [13], barley (Hordeum vulgare) [14], rice (Oryza sativa) [15], physic nut (Jatropha curcas) [16], maize (Zea mays) [17], wheat (Triticum aestivum) [18], cotton (Gossypium hirsutum) [19] and so on (Table 1).…”
Section: Classification and Diversification Of Wrky Genes Familymentioning
confidence: 99%
“…In sugarcane, a WRKY-IIc TF gene ScWRKY3 played positive regulation by sodium chloride (NaCl), polyethylene glycol (PEG), and abscisic acid (ABA), but it was suppressed by salicylic acid (SA) and methyl jasmonate (MeJA) [38]. In other crops, overexpression of TaWRKY93 [39], ZmWRKY40 [17], TaWRKY2 [40], GhWRKY91 [41] and GmWRKY54 [42] conferred drought tolerance through ABA, Ca 2+ -mediated signal transduction pathways and osmotic adjustments.…”
Section: Function and Expression Pattern Of Wrkys Under Abiotic Stressesmentioning
confidence: 99%